Impaired insulin signaling and spatial learning in middle-aged rats: The role of PTP1B - Kuga, Gabriel Keine [UNESP]; Muñoz, Vitor Rosetto; Gaspar, Rafael Calais; Nakandakari, Susana Castelo Branco Ramos; da Silva, Adelino Sanchez Ramos; Botezelli, José Diego; Leme, José Alexandre Curiacos de Almeida; Gomes, Ricardo José; de Moura, Leandro Pereira [UNESP]; Cintra, Dennys Esper; Ropelle, Eduardo Rochete; Pauli, José Rodrigo (Elsevier, 2018)
The insulin and Brain-Derived Neurotrophic Factor (BDNF) signaling in the hippocampus promotes synaptic plasticity and memory formation. On the other hand, aging is related to the cognitive decline and is the main risk factor for Alzheimer's Disease (AD). The Protein-Tyrosine Phosphatase 1B (PTP1B) is related to several deleterious processes in neurons and emerges as a promising target for new therapies. In this context, our study aims to investigate the age-related changes in PTP1B content, insulin signaling, β-amyloid content, and Tau phosphorylation in the hippocampus of middle-aged rats. Young (3 months) and middle-aged (17 months) Wistar rats were submitted to Morris-water maze (MWM) test, insulin tolerance test, and molecular analysis in the hippocampus. Aging resulted in increased body weight, and insulin resistance and decreases learning process in MWM. Interestingly, the middle-aged rats have higher levels of PTP-1B, lower phosphorylation of IRS-1, Akt, GSK3β mTOR, and TrkB. Also, the aging process increased Tau phosphorylation and β-amyloid content in the hippocampus region. In summary, this study provides new evidence that aging-related PTP1B increasing, contributing to insulin resistance and the onset of the AD.
Keywords: Aging; BDNF; Hippocampus; Insulin; PTP1B